1997
DOI: 10.1155/1998/395297
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocyte Immunity in Host Defence against Chlamydia trachomatis and Its Implication for Vaccine Development

Abstract: Chlamydia trachomatis is an obligate intracellular bacterial pathogen that causes several significant human infectious diseases, including trachoma, urethritis, cervicitis and salpingitis, and is an important cofactor for transmission of human immunodeficiency virus. Until very recently, over three decades of research effort aimed at developing a C trachomatis vaccine had failed, due mainly to the lack of a precise understanding of the mechanisms for protective immunity. Although most studies concerning protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 123 publications
(117 reference statements)
0
25
0
Order By: Relevance
“…Although the key mechanism underlying the protective responses to Chlamydia is yet to be addressed, significant advances have been made in recent years largely due to the progress in experimental studies using murine models and epidemiological studies in humans (9,10). Chlamydia muridarum, formally called C. trachomatis mouse pneumonitis (MoPn), 2 is commonly used in mouse models of respiratory and genital tract infections (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the key mechanism underlying the protective responses to Chlamydia is yet to be addressed, significant advances have been made in recent years largely due to the progress in experimental studies using murine models and epidemiological studies in humans (9,10). Chlamydia muridarum, formally called C. trachomatis mouse pneumonitis (MoPn), 2 is commonly used in mouse models of respiratory and genital tract infections (10).…”
mentioning
confidence: 99%
“…Chlamydia muridarum, formally called C. trachomatis mouse pneumonitis (MoPn), 2 is commonly used in mouse models of respiratory and genital tract infections (10). It has been demonstrated that the pattern of cytokine responses is important in the regulation of immune responses to Chlamydia (11,12), and T cell-mediated immunity is the major protective mechanism against chlamydial infection (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the cytokine patterns have been correlated with the severity of disease progression in both human subjects and animal models. In particular, Th1 responses have been found to be associated with protection, whereas Th2 responses are associated with immunopathology (22)(23)(24)(25)(26). Thus far, there is no report on the role of NKT in chlamydial infection and the effect of NKT on adaptive immune responses to chlamydial infection.…”
mentioning
confidence: 99%
“…It has been suggested that cell-mediated immunity, not humoral immunity, plays the dominant role in protective immunity against Chlamydia [12]. The importance of cell-mediated immunity to chlamydial infection has been emphasized in a number of studies [3,7].…”
Section: Introductionmentioning
confidence: 99%